Preliminary investigation on the optimum ultrasound frequency for the degradation of TNT, RDX, and HMX - Ince, E.; Ince, M.; Engin, G. O.; Bayramoglu, M. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2017)
The wastewater of the munitions industry varies in terms of the recalcitrant compounds depending on the products and the manufacturing process. The most commonly encountered energetic nitro-aromatic compounds in ammunition wastewater are trinitrotoluene (TNT), nitro-heterocyclic hexahydro-trinitrotriazine (RDX), and cyclotetramethylene-tetranitramine (HMX). These compounds are known to be very toxic and resistant to biodegradation. The aim of this study was to determine the appropriate ultrasound frequency to assist the anaerobic biodegradation of TNT, RDX, and HMX Therefore, the optimum ultrasound frequencies were investigated to degrade TNT, RDX, and HMX without destroying anaerobic microorganisms. The results showed that ultrasound irradiation was effective for the degradation of all the explosive compounds used. However, the maximum removal efficiencies and minimum microorganism lysis were achieved by the frequencies of 20 and 800 kHz.
Keywords: TNT; RDX; HMX; Ultrasound; Frequency; BIODEGRADATION; PRETREATMENT; ENHANCEMENT; CAVITATION; SONICATION; REACTOR; SLUDGE; WATER; POWER; Environmental Sciences & Ecology